Development and Maintenance of Self-Disclosure on Facebook: The Role of Personality Traits. (June 2019) - Caci, Barbara; Cardaci, Maurizio; Miceli, Silvana
This study explored the relationships between Facebook self-disclosure and personality traits in a sample of Italian users. The aim was to analyze the predictive role of Big Five personality traits on different parameters of breadth and depth of self-disclosed behaviors online. Facebook users, aged between 18 and 64 years of age ( M age = 25.3 years, SD = 6.8; N = 958), of which 51% were female, voluntarily completed an online survey assessing personality traits and Facebook self-disclosure. Results at a series of hierarchical regression analyses significantly corroborated the hypotheses that high extroverted and openness people tend to disclose on Facebook a significant amount of personal information, whereas high consciousness and agreeableness users are less inclined to do it. Furthermore, more extroverts and agreeableness people develop less intimacy on Facebook, differently from those with high levels of openness. Results also corroborated the hypothesis of a full mediation of time usage in the relationship between personality factors such as extroversion and conscientiousness with breadth of Facebook self-disclosure. Overall, according to the findings of the current study, personality traits and Facebook self-disclosure become central both as predictive variables for depicting the different profiles of potential addicted and as variables to help educators, teachers, and clinicians to develop training or therapeutic programs aimed at preventing the risk of Internet addiction. Limitations of the study are discussed, and directions for future research are suggested.